E.163 1945 "Emergency Standard Specification for Dwellinghouse Construction" – a forgotten ancestor - Isaacs, Nigel (Architectural History Aotearoa, 2024)
The outbreak of World War II led to a focus on the most efficient use of materials within New Zealand. In 1944 the New Zealand Standards Council was requested to develop an "Emergency Standard Specification for Dwellinghouse Construction." Unlike NZSS 95 "New Zealand Standard Model Building By‐Law" which was limited to structural stability, public health and other council‐controlled issues, this new specification (NZSS E.163) could deal with materials and construction methods. Published in January 1945, only two copies appear extant – a partial copy in Wellington City Archives and a full copy in Auckland City Archives, although the Committee minutes are held in Archives New Zealand. As well as dealing with house construction (foundations, concrete work, carpentry, etc.) it deals with internal finishing (solid‐ and fibrous‐plaster, terrazzo, painting and paperhanging, etc.) and services (plumbing, drainage and electrical). E.163 was promoted as being of real benefit to occupants (owners or tenants) as they could be assured as to "essential considerations relating to materials, workmanship, and design" – placing quality, not speed at the heart of the then Government’s actions. The paper compares the requirements of E.163 with the relevant parts of NZSS95, as well as exploring its relationship to NZS 3604 "Code of Practice for Light Timber Frame Buildings Not Requiring Specific Design" and modern model specifications.